2021
DOI: 10.26717/bjstr.2021.38.006120
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Developed Sensorimotor Therapy Device: Synchronous Inputs of Visual Stimuli and Vibration to Improve Recovery of Distal Radius Fractures

Abstract: Every fracture requires immobilization following surgery; however, immobilization impairs tactile perception and consequently diminishes cortical somatosensory maps. To minimize this adverse phenomenon, we developed a prototype device (development code: Ghost) for post-operative use of patients who underwent surgery for distal radius fracture (DRF). Ghost consists of a combination of a visualizer paired with a headmounted display to provide visual stimuli for enhance motor imagery and a vibration motor to prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Bonferroni post-hoc tests showed that the PRWE Total score was 20 [11, 28] (median [25%, 75% quartile]) in the AOT group and 37 [28, 54] in the Non-AOT group at 8 weeks (Z=3.29, p=0.04), the PRWE Specific score was 28 [21, 32] (median [25%, 75% quartile]) in the AOT group and 40 [32, 52] in the Non-AOT group at 4 weeks (Z=3.42, p=0.02), and the PR WE Usual score was 20 [7, 14] (median [25%, 75% quartile]) in the AOT group and 24 [23, 26] in the Non - AOT group at 4 weeks (Z=3.42, p=0.02).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bonferroni post-hoc tests showed that the PRWE Total score was 20 [11, 28] (median [25%, 75% quartile]) in the AOT group and 37 [28, 54] in the Non-AOT group at 8 weeks (Z=3.29, p=0.04), the PRWE Specific score was 28 [21, 32] (median [25%, 75% quartile]) in the AOT group and 40 [32, 52] in the Non-AOT group at 4 weeks (Z=3.42, p=0.02), and the PR WE Usual score was 20 [7, 14] (median [25%, 75% quartile]) in the AOT group and 24 [23, 26] in the Non - AOT group at 4 weeks (Z=3.42, p=0.02).…”
Section: Resultsmentioning
confidence: 99%
“…AOT can consist of first-person and third-person action observations,but the first-person motion illusion is easier to produce than the third-person motion illusion, and the sense of bodily ownership of the hand on the screen is higher, as evidenced by the activity of the cerebral motor-related regions in near-infrared spectroscopy [25] . Thus, we employed an HMD-based first-person action observation system [26] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation